From Hospital to the Community: Redesigning the Human Immunodeficiency Virus (HIV) Clinical Service Model to Respond to an Outbreak of HIV Among People Who Inject Drugs. (2nd September 2020) - Metcalfe, Rebecca; Ragonnet-Cronin, Manon; Bradley-Stewart, Amanda; McAuley, Andrew; Stubbs, Harrison; Ritchie, Trina; O'Hara, Regina; Trayner, Kirsten; Glover, Claire; Laverty, Lynn; Sills, Laura; Brown, Kathryn; et al.
Abstract: An outbreak of human immunodeficiency virus (HIV) among people who inject drugs in Glasgow, Scotland started in 2014. We describe 156 cases over 5 years and evaluate the impact of clinical interventions using virological and phylogenetic analysis. We established (1) HIV services within homeless health facilities, including outreach nurses, and (2) antiretroviral therapy (ART) via community pharmacies. Implementation of the new model reduced time to ART initiation from 264 to 23 days and increased community viral load suppression rates to 86%. Phylogenetic analysis demonstrated that 2019 diagnoses were concentrated within a single network. Traditional HIV care models require adaptation for this highly complex population.